Minimal Clinically Important Difference on Parkinson's Disease Sleep Scale 2nd Version. (11th October 2015) - Horváth, Krisztina; Aschermann, Zsuzsanna; Ács, Péter; Deli, Gabriella; Janszky, József; Komoly, Sámuel; Karádi, Kázmér; Kovács, Márton; Makkos, Attila; Faludi, Béla; Kovács, Norbert
Abstract : Background and Aims . The aim of the present study was to determine the estimates of minimal clinically important difference for Parkinson's Disease Sleep Scale 2nd version (PDSS-2) total score and dimensions. Methods . The subject population consisted of 413 PD patients. At baseline, MDS-UPDRS, Hoehn-Yahr Scale, Mattis Dementia Rating Scale, and PDSS-2 were assessed. Nine months later the PDSS-2 was reevaluated with the Patient-Reported Global Impression Improvement Scale. Both anchor-based techniques (within patients' score change method and sensitivity- and specificity-based method by receiver operating characteristic analysis) and distribution-based approaches (effect size calculations) were utilized to determine the magnitude of minimal clinically important difference. Results . According to our results, any improvements larger than −3.44 points or worsening larger than 2.07 points can represent clinically important changes for the patients. These thresholds have the effect size of 0.21 and −0.21, respectively. Conclusions . Minimal clinically important differences are the smallest change of scores that are subjectively meaningful to patients. Studies using the PDSS-2 as outcome measure should utilize the threshold of −3.44 points for detecting improvement or the threshold of 2.07 points for observing worsening.